The ambiguity of teaching to the test : standards, assessment, and educational reform - Firestone, William A.; Monfils, Lora Frances; Schorr, Roberta Y. (L. Erlbaum Associates Publishers, 2004)
This work offers a hard look at the effects of state testing, and thoroughly examines the ambiguity of test preparation and how test preparation practices are influenced by what teachers know and the leadership coming from the school and district.